Basic Trends of Information Society Development in Russia Compared to World's Leading Countries - Sadovnikova, Natalia Alekseevna; Klochkova, Elena Nikolaevna; Dobrolyubova, Elena Igorevna; Alexandrov, Oleg Vladimirovich (International Review of Management and Marketing, 2015)
The market of information technologies (hereinafter referred to as IT) is one of the most dynamically developing markets in the global economy and public relations. The information society indicators are dynamically changing not only in the Russian Federation but in most foreign countries; competitive struggle for the presence on the international market of companies from some or other countries is strengthening. In that connection, regular assessment of efficiency and performance of governmental programs and strategies implementation in the information society is an important factor creating the conditions for keeping and improving Russia's competitive advantages in the global IT market. In connection with the above, the objective of this article is to study the basic trends of the global information society development, finding Russia's place in the global ratings by the basic indicators of the sector and finding key problems and ways to solve them. Keywords: information and communication technologies (ICT), media environment, IT sector, information security, e-government. JEL Classifications: D83; F21; H11; O32; O33; O24; O38; O43; R58